Quality Improvement of Public Services in Surabaya Radio Frequency Spectrum Monitoring Office with Integration of Service Quality, Important Performance Analysis and House of Quality - Pribadi, Henry; Suef, Mokhamad (Institut Teknologi Sepuluh Nopember, 2020)
The purpose of frequency spectrum management is to be effective, efficient, and free interferrence in frequency usage. As a Ministry Technical Unit, Balmon Surabaya has the task to supervise and controll the frequency usage in East Java. In carrying out their duties, there are some user’s complaints about Balmon Surabaya services. Therefore it is necesary to improve the quality of service and to know what service factors affecting the customers satisfaction. Objective of this research is to determine the quality of services and technical response that should be done in accordance with expectations of customers. The services as the object of the research are Radio Station License Distribution, Payment Notification Letter Distribution, and Interferrence of Frequency Report Handling. Measurement of the service is performed using Servqual methode while determining the variable to be improved use Important Performance Analysis. Then, Quality Function Deployment is utilized to develop the technical response influencing the service quality. The result shows that the highest gap is providing the free-toll telephone line, the 2nd is mentioning the data/references in giving the informations, and the 3rd is distributing the Payment Notification Letter before the due date. The Importance- Performance Analysis shows that there are 3 variabels in Quadrant I, distributing the Payment Notification Letter before the due date, mentioning the data/refferences in giving the informations, and providing of free-toll telephone line. QFD reveals that there are 3 Technical Responses with highest value of Important Rating of ie., the printing the Payment Notification Letter 2 months before the due date; confirming the letter receipt by the user, and proposing the toll-free number